The Effect of Transformational Leadership and Organizational Citizenship Behavior on Employee Performance in ABC Hotel - Ismail, Fadillah; Shi, Chan Yet; Wei, Chan Shiau (Journal of Human Capital Development (JHCD), 2025)
Transformational leadership and organizational citizenship behavior (OCB) are critical elements to enhance employee performance in an organization. However, nearly 90% of hotel had to lay off globally due to the COVID-19 pandemic. Malaysia’s leadership also has been out of focus for many years and most of the organizations do not realize the importance of OCB in the workplace. Hence, the objectives of this research are to measure the level of employee performance, and to identify the relationship and the effect of transformational leadership and OCB on employee performance in ABC Hotel. The research was a cross-sectional study and a quantitative method was utilized. The questionnaire was adopted from previous research while the validity and reliability were shown in a high level. The data was collected through Google Forms from 122 employees in the target population by using stratified random sampling. The return rate reached 95.08%. The results of the current study provide empirical evidence on key issues related to transformational leadership and OCB of employees in ABC Hotel. Findings have shown a high level of employee performance with a positive relationship between transformational leadership (r=0.742) and OCB (r=0.638) with employee performance. The main result also showed that transformational leadership (r2=0.759) and OCB (r2=0.688) have a significant effect on employee performance. In conclusion, this research provides clear direction to stakeholders on the existing transformational leadership and OCB for the improvement in employee performance at ABC Hotel and other private sectors.